Garlic extract (Allium sativum) improves the taste of dried moringa noodle products (Moringa oleifera) - Junie Suriawati; Siti Rahayu Rachmawati (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Moringa leaves are plants that have antioxidants and are rich in nutritional value. Panelists said they liked the aroma and taste parameters of dried moringa noodles by adding moringa leaf extract using the pressing method. Adding garlic is needed to cover the aroma and taste because garlic has a distinctive and robust flavor component. The purpose was to improve the taste of dried moringa noodles by adding garlic extract. This experimental research was a completely randomized design. Dried moringa noodles were obtained by adding garlic extract concentrations of 0% (F0), 5%(F1), 10%(F2), and 15%(F3). The hedonic test used 30 untrained panelists with parameters of taste, aroma, color, and texture. The hedonic data were tested for normality using the Kolmogorov-Smirnov test, followed by the ANOVA nova test. If there was a significant difference, continued by the Duncan test with 95% CI. The results of the hedonic test of dry moringa noodles with the addition of garlic extract for taste (p=0,000) showed panelists preferred dry moringa noodles F1 and aroma (p=0,113), color (p=0,104), and texture (p=0,081) there was no significant difference for the treatment of adding garlic extract. F1 dry moringa noodles are safe to use as a food ingredient and contain nutritional value. In conclusion, adding garlic extract can improve the taste of dry moringa noodles (F1).